SETUBUH DUA WANITA - Dewi Susanti (LPPMPP Institut Seni Indonesia Padangpanjang, 2011)
The choreography “Two Women Intercourse” is inspired by the increasingly common social phenomena called lesbianism. The basis of its gestures derives from Malay and Minang traditional dances with contemporary touches to easily communicate it to its audience. The dance is choreographed using an environmental choreographing technique that involves ten dancers consisting of two male dancers and eight female dancers. Expressing the idea of lesbianism the dance “Two Women Intercourse” is tinged with the soul expression resulting from the real world story of some choreographer’s friends. The choreography is performed in a cafe called Bambo Resto Yogyakarta in order to accommodate the glamour and the freedom of night life. The phenomena of lesbianism is more clearly observed in certain community that often organize the meeting in the cafes considered to be public space with high privation as modernity icon. The atmosphere of the Bambo Resto cafe is highly relevant to the theme of the choreography and its architecture as well as its landscape are used to support the necessity of chorographical aesthetics.